PEMBERDAYAAN UMKM MELALUI PELATIHAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BERBASIS SAK EMKM - Oscar Chrismadian Noventa; Ignatius Novianto Haribowo; Martinus Parnawa Putranta; Ch. Heni Kurniawan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia’s economy; however, many business actors still face challenges in basic bookkeeping and preparing reliable financial statements. This article reports a community service program conducted at Saint Joseph (Santo Yusup) Parish, Bintaran, Yogyakarta, which provided training and assistance in preparing financial statements based on SAK EMKM using Microsoft Excel. The program was carried out in seven sessions, including three intensive coaching sessions, from October 2025 to February 2026, and was attended by 63 MSME participants. It was followed by one month of mentoring to strengthen participants’ understanding. The results indicate an improvement in participants’ understanding of SAK EMKM, as well as their ability to record transactions and prepare simple financial statements. However, the use of Microsoft Excel remains a major challenge for some participants. Overall, the program encourages more systematic bookkeeping and enhances MSMEs’ readiness to access financing.